Peran Pengajaran Membaca dan Menulis dalam Meningkatkan Kemampuan Menulis Esai Argumentasi - Ari Prayogi; Yeti Mulyati; Andoyo Sastromiharjo; Vismaia S. Damaianti (Universitas Mulawarman, 2023)
The purpose of this study was to investigate the effectiveness of teaching reading and writing skills based on critical thinking skills in improving argumentative essay writing skills. Quasi-experimental was used as a research method involving 250 high school level students, divided into experimental and control groups, each consisting of 125 students. The experimental group received an instructional design intervention, while the control group received regular intervention in writing argumentative essays. The research findings show first that this instructional design can improve the ability to write argumentative essays. Depth, logical organization, and criticality, cohesion, coherence, and the use of language used in writing argumentation essays have increased. In addition, instructional design is also able to improve students' critical thinking skills. The improvement of students' critical thinking skills can be seen in the ability to analyze and evaluate the logic used in argumentative essays. So, the integration of reading, writing, and critical thinking skills can improve the ability to write argumentative essays, students' critical thinking, and student attitudes and responses.